Second world record for two Calvatia species (Agaricaceae: Basidiomycota) - A. S. Ferreira-Sá; L. Leonardo-Silva; V. G. Cortez; S. Xavier-Santos (Brazilian Journal of Biology, 2021)
Abstract Calvatia is a genus of gasteroid fungi, comprising about 47 species worldwide. In this paper we report the second worldwide occurrence of two poorly known species of Calvatia, recorded in the Cerrado biome of Brazil: C. oblongispora and C. nodulata. Detailed morphological descriptions and illustrations, including scanning electron micrographs of hyphae and basidiospores are provided, as well a discussion on their taxonomy and geographic distribution.